TP009/#1444 Compare surgical staging with imaging in locally advanced cervical cancer: a multicenter, phase III trial. (4th December 2022) - He, Misi; Wang, Haixia; Guo, Mingfang; Wang, Ling; Tang, Ying; Zhou, Qi; Zou, Dongling
Abstract : Objectives: Determining para-aortic lymph node (PALN) status is the most important prognostic factor and a key point for the therapeutic strategy in locally advanced cervical cancer (LACC). When positive PALN is diagnosis, radiotherapy is extended to the para-aortic area. The radiation planning may be based on image staging while others recommend to rely on surgical. The gold standard to identify para-aortic extension is histological evaluation of PALN, but the survival benefit of surgical staging remains controversial. This study is a national, prospective, multicenter and non-randomized clinical trial evaluating the survival impact of surgical staging in patients with LACC. Methods: Eligible patients present with FIGO (2018) stage IB3, IIA2, IIB-IVA (excluded IIIC2r) and histologically confirmed cervical squamous cell carcinoma, adenocarcinoma, adeno-squamous cell carcinoma. According to patient's willing, 1956 patients will be non-randomized to receive either CCRT (Pelvic EBRT/Extended-field EBRT + cisplatin (40 mg/m2) or carboplatin (AUC=2) every week for 5 cycles + brachytherapy) or Open/minimally invasive PALN dissection followed by CCRT. The primary endpoint is PFS. Secondary endpoints are OS, surgical complications, imaging sensitivity and specificity. The sample size calculation of 1663 patients provides 90% power to detect a difference in survival at the two-sided 1% significance level using the log-rank test, considering a 15% reduction, a total of 1956 patients are required. This study began in June 2022 and will be accrued within 5 years. Enrollment is ongoing. Results: Trial in progress: there are no available results at the time of submission. Conclusions: Trial in progress: there are no available conclusions at the time of submission.